EFFECTIVENESS OF FOREST CONSERVATION PARTNERSHIP PROGRAM AND ITS ECONOMIC IMPACT ON COMMUNITIES IN KARANG GADING WILDLIFE SANCTUARY AND NORTHEAST LANGKAT - Lusiana Simatupang; Tri Martial; Lindawati (Agrisaintifika: Jurnal Ilmu-Ilmu Pertanian, 2026)
Forest conservation partnerships are designed to reconcile protected-area management with local livelihood needs. This study analyzed the implementation, effectiveness, and economic impacts of the Forest Conservation Partnership Program in the Karang Gading and Langkat Timur Laut Wildlife Reserve, North Sumatra, Indonesia. A descriptive quantitative approach was used and supported by qualitative information from interviews, field observation, and program documents. Primary data were collected from 45 purposively selected respondents involved in or familiar with the partnership program. Program effectiveness was measured using a five-point Likert scale covering community participation, partnership institutions, area sustainability, implementation of conservation activities, and economic impacts. Income differences before and after the program were analyzed using the Wilcoxon signed-rank test because the income data were not normally distributed. The results show that the overall program effectiveness index reached 85.92%, categorized as highly effective. The strongest dimensions were area sustainability (86.86%) and partnership institutions (86.78%), followed by conservation activity implementation (86.37%), community participation (84.98%), and economic impact (84.59%). Average monthly income increased from IDR 2,533,333 to IDR 3,258,889, with 44 respondents experiencing income gains and one respondent reporting no change. The Wilcoxon test indicated a statistically significant income difference (Z = -5.922; p < 0.001). The findings suggest that conservation partnerships can simultaneously strengthen mangrove conservation governance and improve community livelihoods, although market access, enterprise capacity, and benefit distribution require further policy support.